Evaluation of the Use of Water Quality Videotapes by County Extension Offices in Iowa - Julia Gamon; Roger Roe; S. Michael Campbell (Journal of Applied Communications, 1994)
All of the 100 county Extension offices in Iowa have a set of six water quality videotapes available for use by clientele.